Systematic Review of Phytotherapeutic Treatments for Different Farm Animals Under European Conditions - Tamminen, Lena-Mari; Emanuelson, Ulf; Blanco-Penedo, Isabel (Frontiers in Veterinary Science, 2018)
The emergence and spread of antibiotic resistance is a growing global threat and has aroused a global interest in limiting antibiotic use in animal agriculture. As we are entering the post-antibiotic era, there is a growing need for identifying alternatives to antibiotics for prevention and treatment. Although phytotherapeutic remedies are available and are used in Europe, evidence of their efficacy is currently very limited but is nevertheless still necessary. A systematic review of phytotherapy used for the treatment and prevention of infectious diseases in farm animals has been conducted using the PICOS approach. Analysis and extraction of information from studies was performed according to a protocol, and included: publication year and source, research body, species, farming system, purpose of application, disease in focus, diagnostic method, remedy used (origin and ingredients of the remedy), producer of remedy, way of administration, study design and control groups, measure of effect and outcome of the study. A total of 1,705 papers were screened, but only 44 (comprising 53 independent studies) met the inclusion criteria. The majority of the scientific studies identified show limitations in the study design as well as in presentation and standardisation of the botanical remedies studied, which limits the possibilities of drawing firm conclusions. Preventive effect was investigated in 89% of the studies. Half of the studies reported uncertain effects of the botanical remedies on subclinical measures in comparison to a control group. The review highlights unresolved questions such as the need for standardized controlled trials and for improved standardization of the botanical products by analytical methods, such as high-performance liquid chromatography. It is necessary to consider this in order to achieve replicable outcomes and establish efficacy and safety of phytotherapy in farm practice. The manageability of alternative medicine in farm animals also warrants further investigation so as to ascertain whether all necessary preconditions for their use are being granted.